127k views
1 vote
I need help! Can you explain you got this?

I need help! Can you explain you got this?-example-1

1 Answer

5 votes

9514 1404 393

Answer:

y: 0, 6, 12, 18, 24

Explanation:

Put the value of x in the equation and do the arithmetic.

For x = -1,

y = 6(-1) +6

y = -6 +6 = 0

For x = 0,

y = 6(0) +6

y = 0 +6 = 6

If you're paying attention, you can see that increasing x by 1 will make the value of y go up by 6. We can see the values of x increase by 1 from each to the next. This means the y numbers on the bottom row increase by 6 from each to the next:

x: -1, 0, 1, 2, 3

y: 0, 6, 12, 18, 24

User Fruggiero
by
5.5k points